2020
DOI: 10.1007/s00406-020-01120-3
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to common infections and risk of suicide and self-harm: a longitudinal general population study

Abstract: Common infectious agents, such as Toxoplasma gondii (T. gondii) and several human herpes viruses, have been linked to increased risk of self-harm. The aim of this study was to investigate the associations between self-harm and seropositivity to T. gondii, Epstein-Barr virus (EBV), Herpes Simplex virus Type 1 (HSV-1), and Cytomegalovirus (CMV). IgM and IgG antibodies to these infections were measured in the Health 2000 project nationally representative of the whole Finnish adult population, and 6250 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
(108 reference statements)
0
9
1
Order By: Relevance
“…The highlighted inflammatory pathways and associated chemical compounds affecting the nervous system can play key roles in behavioral development that triggers suicide attempts ( 64 , 65 ). In contrast, the current results deny associations between T. gondii infection and suicidal attempts discovered in a study on patients suffering from mental and behavioral disorders due to psychoactive substance use in Mexico ( 66 ), adolescents in Turkey ( 67 ) and general population study in Finland ( 68 ). Further studies with a wide range of sociodemographic, clinical and behavioral variables are necessary to investigate associations between T. gondii infection and suicide attempts.…”
Section: Discussioncontrasting
confidence: 95%
“…The highlighted inflammatory pathways and associated chemical compounds affecting the nervous system can play key roles in behavioral development that triggers suicide attempts ( 64 , 65 ). In contrast, the current results deny associations between T. gondii infection and suicidal attempts discovered in a study on patients suffering from mental and behavioral disorders due to psychoactive substance use in Mexico ( 66 ), adolescents in Turkey ( 67 ) and general population study in Finland ( 68 ). Further studies with a wide range of sociodemographic, clinical and behavioral variables are necessary to investigate associations between T. gondii infection and suicide attempts.…”
Section: Discussioncontrasting
confidence: 95%
“…In contrast, our results agree with a lack of association between T. gondii exposure and suicidal ideation found in a study of patients suffering from mental and behavioral disorders due to psychoactive substance use in Mexico [ 22 ], and a lack of association between T. gondii seropositivity and suicide attempts in adolescents in Turkey [ 23 ]. In addition, in a longitudinal general population study in Finland, suicidal outcomes were not associated with T. gondii seropositivity [ 24 ]. The negative result found in the present study does not indicate that there is not any association between T. gondii infection and completed suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Another study assessed the role of common infections on suicidality and revealed that common infections have no influential role on suicide and suicidal behavior. 10 However, the role of inflammation and increased level of CRP has been noted in an other study. 11 It has been postulated that chronic inflammatory response could have roles in influencing the suicidal behavior.…”
Section: Discussionmentioning
confidence: 82%